2018
DOI: 10.1051/kmae/2018017
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of expansive, bloom-forming algaeGonyostomum semenvs.plankton community and water chemistry in four small humic lakes

Abstract: One of the features of Gonyostomum semen, a bloom-forming and expansive flagellate, is uneven distribution in the vertical water column often observed in humic lakes. In this paper, we analysed vertical distribution of the algae in four small (0.9–2.5 ha) and humic (DOC: 7.4–16.5 mg dm−3) lakes with similar morphometric features with the aim to test the hypothesis that vertical distribution of G. semen may be shaped by zooplankton structure and abundance. In addition, we wanted to check whether high biomass of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…However, larger cladocerans experienced difficulty feeding in the presence of cyanobacteria because they do not feed selectively, and longer algae filaments clog their filtering apparatuses [56][57][58][59]. The mass development of inedible algae Gonyostomum semen is a common phenomenon in humic lakes in NE Poland [15,60,61], and the lakes from G4 were eutrophic and dominated by cyanobacteria. Therefore, inedible algae or cyanobacteria could be the main factor that favors small zooplankton species in these lakes because they are better competitors than large herbivorous filterfeeders in the presence of large inedible algae [62].…”
Section: Discussionmentioning
confidence: 99%
“…However, larger cladocerans experienced difficulty feeding in the presence of cyanobacteria because they do not feed selectively, and longer algae filaments clog their filtering apparatuses [56][57][58][59]. The mass development of inedible algae Gonyostomum semen is a common phenomenon in humic lakes in NE Poland [15,60,61], and the lakes from G4 were eutrophic and dominated by cyanobacteria. Therefore, inedible algae or cyanobacteria could be the main factor that favors small zooplankton species in these lakes because they are better competitors than large herbivorous filterfeeders in the presence of large inedible algae [62].…”
Section: Discussionmentioning
confidence: 99%
“…This species could be considered a valuable food source due to its high concentration of polyunsaturated fatty acids (especially EPA and C18 PUFAs), but it is too large for most zooplankton to ingest 33 . However, some species such as Asplanchna priodonta , Eudiaptomus gracilis and Holopedium gibberum can feed on G. semen at high rates 17 , 34 . The results of our study suggest that A. priodonta could have an advantage over other zooplankton species during the domination of G. semen in phytoplankton, while E. gracilis and H. gibberum were negatively related to G. semen biomass.…”
Section: Discussionmentioning
confidence: 99%
“…The well‐oxygenated hypolimnion in oligotrophic lakes creates favorable habitat for large cold‐water species and increases zooplankton species richness, which further promotes the effective transfer of matter (Karpowicz, Ejsmont‐Karabin, et al., 2020). Decreases in TTE can also be attributed to an increase in inedible algae in the eutrophic lakes, which were dominated by filamentous cyanobacteria, while in dystrophic lakes there was commonly mass development of the large raphidophyte Gonyostomum semen (Pęczuła et al., 2018). Therefore, our study indicated that different disturbances like eutrophication and dystrophication similarly decrease the TTE of matter between phytoplankton and zooplankton.…”
Section: Discussionmentioning
confidence: 99%